Carbon Emission Intensity and Bioactive Compound Quality in Organic vs. Conventional Emprit Ginger (Zingiber officinale var. amarum): A Life Cycle Assessment Approach - Andreas Petra Wibiantoro; Maria Marina Herawati; Bistok Hasiholan Simanjuntak (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Agricultural intensification drives environmental degradation, yet LCA studies often overlook carbon uptake and phytochemical quality. Objective: This study critically evaluates the trade-offs between environmental performance and functional quality in emprit ginger (Zingiber officinale var. amarum) cultivation under organic and conventional farming systems. While most previous studies emphasize greenhouse gas (GHG) emissions, this research integrates carbon footprint, carbon uptake proxies, and bioactive compound analysis within a unified framework using Life Cycle Assessment (LCA). Methods: A quantitative approach was employed combining cradle-to-grave LCA (ISO 14040 standard) with laboratory-based measurements of ash content and gingerol concentration. Primary data were obtained through field sampling and laboratory analysis, while secondary data were collected via structured farmer interviews to construct the life cycle inventory. Statistical differences between systems were assessed using independent t-tests. Results: The results demonstrate that organic cultivation significantly reduces carbon emission intensity (462.13 kg CO₂ ha⁻¹ ton⁻¹) compared to conventional practices (525.12 kg CO₂ ha⁻¹ ton⁻¹), primarily due to the exclusion of synthetic nitrogen fertilizers. Beyond environmental performance, organic systems produced significantly higher concentrations of gingerol (1.4068% w/w) and shogaol (0.0363% w/w), indicating enhanced secondary metabolism. Higher ash content in organic ginger further suggests improved mineral uptake and physiological activity associated with biomass carbon accumulation. Conclusion: These findings suggest that organic systems can simultaneously reduce emissions and improve product quality, supporting climate-smart agriculture and sustainable intensification in high-value horticultural crops.